Association of HIV Education with HIV Testing and Sexual Risk Behaviors among U.S. Youth, 2009–2017: Disparities Between Sexual Minority and Sexual Majority Youth - Phillips, Gregory (Prev Sci, 2020)
HIV remains a serious concern among youth, particularly among sexual minority youth (SMY). Risk behaviors including low rates of HIV testing and inconsistent condom use as well as use of substances before sex contribute to these disparities. Therefore, HIV education in schools may be a valuable tool for reducing HIV-related risk behaviors. Using a large, pooled sample of youth (N=169468) from the 2009 –2017 Youth Risk Behavior Survey (YRBS), we conducted the first population-level assessment of associations between HIV education and risk behavior prevalence among high school aged youth by sexual behavior (i.e., sex of sexual partner[s]) in the US. Results demonstrated that racial/ethnic minority youth and SMY were less likely to have received HIV education than White or heterosexual peers. HIV education was associated with less substance use at last sex. Among males, HIV education was associated with increased condom use and HIV testing, emphasizing its promise as a potential intervention for risk behavior reduction. Results are discussed in light of current literature with future recommendations.